Risk factors of amyotrophic lateral sclerosis: a global meta-summary - Duan, Qing-Qing; Jiang, Zheng; Su, Wei-Ming; Gu, Xiao-Jing; Wang, Han; Cheng, Yang-Fan; Cao, Bei; Gao, Xia; Wang, Yi; Chen, Yong-Ping (Frontiers in Neuroscience, 2023)
Background The etiology of amyotrophic lateral sclerosis (ALS) remains largely unknown. This study aimed to summarize the relationship between ALS and its genetic and non-genetic risk factors. Method A search of relevant literature from PubMed, Embase, and Cochrane Database from inception to December 2022 was performed. Random-effects or fixed-effects models were performed by Stata MP 15.0 to pool multivariate or adjusted ratios (OR). PROSPERO registration number: CRD42022301549. Results 230 eligible studies were included, of which 67 involved 22 non-genetic factors, and 163 involved genetic factors. Four aspects of non-genetic factors, including lifestyle, environmental and occupational exposures, pre-existing diseases/comorbidity and medical exposures, and others, were analyzed. Exposure to heavy metals (OR = 1.79), pesticides (OR = 1.46), solvents (OR = 1.37), previous head trauma (OR = 1.37), military service (OR = 1.29), stroke (OR = 1.26), magnetic field (OR = 1.22) and hypertension (OR = 1.04) are significant risk factors, but use of antidiabetics (OR = 0.52), high BMI (OR = 0.60 for obese and overweight vs. normal and underweight), living in urban (OR = 0.70), diabetes mellitus (OR = 0.83), and kidney disease (OR = 0.84) decrease the risk for ALS. In addition, eight common ALS-related genes were evaluated, the mutation frequencies of these genes were ranked from highest to lowest as SOD1 (2.2%), C9orf72 (2.1%), ATXN2 (1.7%), FUS (1.7%), TARDBP (0.8%), VCP (0.6%), UBQLN2(0.6%) and SQSTM1 (0.6%) in all the ALS patients. Conclusions Our findings suggested that effective intervention for risk exposure and timely modification of lifestyle might prevent the occurrence of ALS. Genetic mutations are important risk factors for ALS and it is essential to detect genetic mutations correctly and scientifically. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=301549, identifier: CRD42022301549.